The effects of acupressure on sleep quality and compassion fatigue among emergency and critical care nurses during the coronavirus disease 2019 pandemic: A clinical trial - Sajad Abasi; Hossein Akbari; Mahdieh Sabery (Kashan University of Medical Sciences, 2022)
Background: Sleep disorders and compassion fatigues are two main physical and psychological problems among nurses, particularly during the coronavirus disease 2019 (COVID-19) pandemic. Objectives: The aim of this study was to assess the effects of acupressure on sleep quality and compassion fatigue among emergency and critical care nurses during the COVID-19 pandemic. Methods: This randomized controlled trial was conducted in 2020. Participants were eighty nurses recruited from two hospitals in Iran and randomly allocated to control and intervention groups. Acupressure on the Shenmen point was self-administered by participants twice daily for 30 days. The Pittsburg Sleep Quality Index and the Nurses' Compassion Fatigue Inventory were used for data collection before and after the intervention. Data analysis was done using the paired-sample t, independent-sample t, Chi-square, and Mann-Whitney U tests as well as the analysis of covariance. Results: The mean score of the subjective sleep quality, sleep latency, sleep duration, and sleeping medication dimensions of sleep quality significantly decreased in the intervention group (P < 0.05). Moreover, despite no significant between-group difference respecting the pretest mean scores of sleep quality and its dimensions (P > 0.05), the posttest mean scores of sleep quality and its subjective sleep quality, sleep latency, sleep disturbances, and sleeping medication dimensions in the intervention group were significantly less than the control group (P < 0.05). Conclusion: As a noninvasive technique, acupressure can be used to significantly improve sleep quality among nurses during the COVID-19 pandemic.